INCLISIRAN- A breakthrough revolution in the treatment of hypercholesterolemia - Hameed, Ishaque; Samad, Syed Abdus; Khan, Mohammad Omer (Journal of the Pakistan Medical Association, 2022)
We are submitting a Letter to the Editor. It doesn’t require abstract.